Fluorescent transmembrane anion transporters: shedding light on anionophoric activity in cells12. Issue 8 (26th April 2016) - Berry, Stuart N.; Soto-Cerrato, Vanessa; Howe, Ethan N. W.; Clarke, Harriet J.; Mistry, Ishna; Tavassoli, Ali; Chang, Young-Tae; Pérez-Tomás, Ricardo; Gale, Philip A.
Abstract : A series of fluorescent anion transporters have been synthesised and their anion transport properties and interactions with cancer cell lines studied. Abstract : A series of fluorescent anion transporters consisting of a urea or thiourea group linked to a naphthalimide fluorophore have been synthesised and their anion transport properties studied. The compounds possess similar anion transport properties to (thio)urea-based anionophores that have previously been reported. Fluorescence studies in cells show all anionophores cross the plasma membrane and localise within the interior of cells. The most lipophilic, aromatic substituted transporters localise homogeneously throughout the cell and are toxic towards cancer cells with the highly fluorinated compound6 being the most effective. The least lipophilic, alkyl substituted transporters localise in specific vesicles and are non-toxic to cells. This work provides new insight to the actions of anionophores in cells and may be useful in the design of novel antineoplastic agents.